2012
DOI: 10.1021/jp2110067
|View full text |Cite
|
Sign up to set email alerts
|

Cucurbit[8]uril Mediated Donor–Acceptor Ternary Complexes: A Model System for Studying Charge-Transfer Interactions

Abstract: A supramolecular self-assembly approach is described which allows for the convenient preparation of a wide range of charge-transfer (CT) donor-acceptor complexes in aqueous solutions. When one equiv of the macrocyclic host cucurbit[8]uril (CB[8]) is added to an aqueous donor and acceptor solution, a heteroternary complex forms inside the host's cavity with a well-defined face-to-face π-π-stacking geometry of the donor and acceptor. This heteroternary, CB[8]-mediated complex offers the opportunity to study the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
192
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 140 publications
(201 citation statements)
references
References 61 publications
(174 reference statements)
7
192
0
2
Order By: Relevance
“…Compared to other cucurbit[n]urils, Q8 has been studied extensively for its ability to bind two guests simultaneously in aqueous solution (20)(21)(22)(23)(24)(25)(26)(27)(28)(29). Much of our work with Q8 has focused on the molecular recognition of peptides (30)(31)(32)(33)(34)(35)(36).…”
Section: Introductionmentioning
confidence: 99%
“…Compared to other cucurbit[n]urils, Q8 has been studied extensively for its ability to bind two guests simultaneously in aqueous solution (20)(21)(22)(23)(24)(25)(26)(27)(28)(29). Much of our work with Q8 has focused on the molecular recognition of peptides (30)(31)(32)(33)(34)(35)(36).…”
Section: Introductionmentioning
confidence: 99%
“…CB8 has a rather uniform negative electrostatic potential inside the cavity and at the portal area, 18 which probably contributes to the screening of the electrostatic repulsion between the two positively charged guests.…”
Section: Absorption and Fluorescence Characteristics Of Cb8 Complexesmentioning
confidence: 99%
“…17 Biedermann and Scherman demonstrated that the CT excited state is much more efficiently stabilized by the uniform negative electrostatic potential of the CB8 interior than in any polar solvents. 18 They provided evidence for the CB8-promoted CT interaction between guests, and concluded that CT is not the dominant factor in the stabilization of the ternary complexes. The coinclusion of electron-deficient and electron-rich moieties facilitated the creation of host-stabilized supramolecular polymers, 19,20 polyrotaxanes, 21 molecular necklaces, 22 vesicles, 23 and rotaxane dendrimers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These portals narrow the cavity entrance compared to the inner diameter of the cavity (Table 1). [7,9] Electrostatic potential maps show a negative potential at the CB[n] portals, [5,10] which drives the molecular recognition properties by forming charge-dipole and hydrogen bonding interactions with guests. [5,10,11] Much research on CB[n] macrocycles focusses on understanding CB[n]-guest complexation and modulation of the CB[n]-guest binding affinity by external stimuli.…”
Section: Introductionmentioning
confidence: 99%